THE ANGLO-MYSORE WARS: STRATEGY, DIPLOMACY, AND RESISTANCE - Revanasiddappa S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Anglo-Mysore Wars, fought between the Kingdom of Mysore and the British East India Company in the late 18th century, represent a pivotal period in Indian history characterized by intense military conflict, complex diplomacy, and indigenous resistance against colonial expansion. These four wars, spanning from 1767 to 1799, showcased the strategic acumen of Mysore’s rulers—Hyder Ali and his son Tipu Sultan—who challenged British ambitions in southern India with innovative military tactics and savvy diplomatic alliances. Hyder Ali’s rise marked the emergence of Mysore as a formidable power, with a modernized army blending traditional Indian warfare and European military techniques. Under his leadership, and later Tipu Sultan’s, Mysore employed advanced artillery and pioneering rocket technology, which disrupted British forces and underscored the kingdom’s military sophistication. The wars unfolded amidst broader geopolitical tensions, including the global rivalry between Britain and France, with Mysore often allying with the French to counterbalance British dominance. Diplomatically, the Anglo-Mysore Wars highlighted shifting alliances within the Indian subcontinent, involving regional powers such as the Marathas and the Nizam of Hyderabad. The British deftly manipulated these relationships to isolate Mysore, demonstrating the intricate interplay of local and imperial politics. Despite several tactical successes and treaties that temporarily restored peace, Mysore ultimately succumbed to the combined pressure of British military campaigns and diplomatic coalitions. Beyond military engagements, the wars had profound socio-economic impacts on Mysore, affecting agriculture, trade, and society. Tipu Sultan’s rule also emphasized cultural and ideological resistance, blending religious identity with pragmatic governance to unify diverse communities against foreign rule. The Anglo-Mysore Wars left a lasting legacy, both in the consolidation of British colonial control in southern India and in inspiring future nationalist movements. They exemplify a critical era of resistance, innovation, and political strategy that shaped the trajectory of Indian history and colonial encounters in the 18th century.